A transcriptomic approach to the metabolism of porphyrin-like pigments in a marine Polychaeta (Eulalia sp.) - Santos, Maria Leonor Veríssimo dos (2021)
The last decade witnessed a growing interest on marine natural pigments for biotechnological and biomedical applications. One of the most abundant naturally occurring pigments are the tetrapyrroles which are prized targets due to their photodynamic properties. Their most notorious representatives are porphyrins. Animal porphyrins result from the breakdown of heme and are known as bile pigments, the best known of which are biliverdin and bilirubin. Because of their unique chemical structure, porphyrins can have several applications such as photosensitizers in photodynamic therapy as well as antioxidants or even antimicrobials. For such reasons, porphyrinoids are high-prized animal metabolites for biomedical research. Naturally, abundant sources of these compounds, particularly those offering a wide-variety of the compounds such as coastal marine invertebrates, yield high biotechnological potential. The Polychaeta Eulalia sp. is known for its bright green coloration provided by the multiple greenish and yellowish porphyrinoid pigments found in this worm, which turns this species into the perfect case study since the chemistry and biosynthetic process of heme-derived pigments in Polychaeta remains mainly unknown. The present study combined HPLC-DAD with a transcriptomic approach (RNA-Seq) on the main tissues of Eulalia sp. displaying pigmentation, the proboscis and epidermis, with the aim of understanding the diversity and origin of its complex pigmentation. The results showed that the endogenous pigments of this worm are seemingly heme-derived and have the necessary mechanism for conversion to bile pigments. Also, several protein variants of the heme biosynthetic pathway were found in the two organs, indicating the possible production of diverse heme related products that can be then converted to products similar to biliverdin or bilirubin. The specific and common variants found in both organs can explain the similar and different pigmentation patterns between the proboscis and epidermis. Altogether, this species is indeed a prolific source of novel porphyrinoids